FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Predicting Cognitive Functioning for Patients with a High-Grade Glioma: Evaluating Different Representations of Tumor Location in a Common Space - S. M. Boelders; W. De Baene; E. Postma; K. Gehring; L. L. Ong (Neuroinformatics, 2024)
Cognitive functioning is increasingly considered when making treatment decisions for patients with a brain tumor in view of a personalized onco-functional balance. Ideally, one can predict cognitive functioning of individual patients to make treatment decisions considering this balance. To make accurate predictions, an informative representation of tumor location is pivotal, yet comparisons of representations are lacking. Therefore, this study compares brain atlases and principal component analysis (PCA) to represent voxel-wise tumor location. Pre-operative cognitive functioning was predicted for 246 patients with a high-grade glioma across eight cognitive tests while using different representations of voxel-wise tumor location as predictors. Voxel-wise tumor location was represented using 13 different frequently-used population average atlases, 13 randomly generated atlases, and 13 representations based on PCA. ElasticNet predictions were compared between representations and against a model solely using tumor volume. Preoperative cognitive functioning could only partly be predicted from tumor location. Performances of different representations were largely similar. Population average atlases did not result in better predictions compared to random atlases. PCA-based representation did not clearly outperform other representations, although summary metrics indicated that PCA-based representations performed somewhat better in our sample. Representations with more regions or components resulted in less accurate predictions. Population average atlases possibly cannot distinguish between functionally distinct areas when applied to patients with a glioma. This stresses the need to develop and validate methods for individual parcellations in the presence of lesions. Future studies may test if the observed small advantage of PCA-based representations generalizes to other data.

Reduced tillage increases soil biological properties but not suppressiveness against Rhizoctonia solani and Streptomyces scabies - Viola Kurm; Mirjam T. Schilder; Wiepie K. Haagsma; Jaap Bloem; Olga E. Scholten; Joeke Postma (Applied Soil Ecology, 2023)

Innovating transcriptomics for practitioners in freshwater fish management and conservation: best practices across diverse resource-sector users - C. A. D. Semeniuk; K. M. Jeffries; T. Li; C. M. Bettles; S. J. Cooke; B. A. Dufour; E. A. Halfyard; J. W. Heath; K. Keeshig; N. E. Mandrak; A. J. Muir; L. Postma; et al. (Reviews in Fish Biology and Fisheries, 2022)

Forgetting the new locations of one’s keys: spatial-memory interference in Korsakoff’s amnesia - Albert Postma; Sascha G. Morel; Margot E. Slot; Erik Oudman; Roy P. C. Kessels (Experimental Brain Research, 2018)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Shared and distinct anatomical correlates of semantic and phonemic fluency revealed by lesion-symptom mapping in patients with ischemic stroke - J. Matthijs Biesbroek; Martine J. E. van Zandvoort; L. Jaap Kappelle; Birgitta K. Velthuis; Geert Jan Biessels; Albert Postma (Brain Structure and Function, 2016)

Objective allergy markers and risk of cancer mortality and hospitalization in a large population-based cohort - Niloofar Taghizadeh; Judith M. Vonk; Jeannette J. Hospers; Dirkje S. Postma; Elisabeth G. E. de Vries; Jan P. Schouten; H. Marike Boezen (Cancer Causes & Control, 2015)

Bactericidal Activity of Lachrymal Secretion and Complement System in Copper Deficient Bovines - Gabriela C. Postma; Leonardo Minatel; Roberto W. I. Olivares; Andrea Schapira; Maria E. Dallorso; Julio C. Carfagnini (Biological Trace Element Research, 2013)

The role of Streptococcus pneumoniae in community-acquired pneumonia among adults in Europe: a meta-analysis - M. H. Rozenbaum; P. Pechlivanoglou; T. S. Werf; J. R. Lo-Ten-Foe; M. J. Postma; E. Hak (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Prevalence of antibodies against Ascaris suum and its association with allergic manifestations in 4-year-old children in the Netherlands: the PIAMA birth cohort study - E. Pinelli; S. M. Willers; D. Hoek; H. A. Smit; L. M. Kortbeek; M. Hoekstra; J. Jongste; F. Knapen; D. Postma; M. Kerkhof; R. Aalberse; J. W. B. Giessen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Improved neuromonitoring during spinal surgery using double-train transcranial electrical stimulation - H. L. Journée; H. E. Polak; M. de Kleuver; D. D. Langeloo; A. A. Postma (Medical & Biological Engineering & Computing, 2004)

Diffusion of new medicines into hospital practice - J. E. F. Zwart-van Rijkom; N. S. Breekveldt-Postma; H.G.M. Leufkens; A. C. G. Egberts (European Journal of Clinical Pharmacology, 2003)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)